Higher-order G-quadruplexes in promoters are untapped drug targets - Monsen, Robert C. (Frontiers in Chemistry, 2023)
G-quadruplexes (G4s) are four-stranded nucleic acid secondary structures that form within guanine-rich regions of chromatin. G4 motifs are abundant in the genome, with a sizable proportion (∼40%) existing within gene promoter regions. G4s are proven epigenetic features that decorate the promoter landscape as binding centers for transcription factors. Stabilizing or disrupting promoter G4s can directly influence adjacent gene transcription, making G4s attractive as indirect drug targets for hard-to-target proteins, particularly in cancer. However, no G4 ligands have progressed through clinical trials, mostly owing to off targeting effects. A major hurdle in G4 drug discovery is the lack of distinctiveness of the small monomeric G4 structures currently used as receptors. This mini review describes and contrasts monomeric and higher-order G-quadruplex structure and function and provides a rationale for switching focus to the higher-order forms as selective molecular targets. The human telomerase reverse transcriptase (hTERT) core promoter G-quadruplex is then used as a case study that highlights the potential for higher-order G4s as selective indirect inhibitors of hard-to-target proteins in cancer.